Comparative cardiovascular outcomes of aripiprazole vs. risperidone in patients with type 2 diabetes and schizophrenia: a retrospective cohort study - Yeh, Yi-Ting; Lo, Shih-Chang; Huang, Chien-Ning; Yang, Yi-Sun; Liao, Pei-Lun; Kornelius, Edy (Frontiers in Pharmacology, 2025)
BackgroundIndividuals with schizophrenia have substantially elevated cardiovascular morbidity and mortality, a disparity further exacerbated by coexisting type 2 diabetes mellitus (T2DM). The impact of specific antipsychotics on long-term cardiovascular outcomes in patients with T2DM remains unclear. We aimed to compare major adverse cardiovascular events (MACEs) in patients with co-occurring T2DM and schizophrenia treated with aripiprazole versus risperidone.MethodsWe conducted a multi-center retrospective cohort study within the TriNetX US Collaborative Network (2014–2024). Adults (≥18 years) with diagnoses of T2DM and schizophrenia who were new users of aripiprazole or risperidone were identified. Aripiprazole and risperidone cohorts were propensity score–matched 1:1 (n = 5,691 each) on demographics (age, sex, race/ethnicity, body mass index), healthcare utilization, socioeconomic and lifestyle factors, comorbidities, and baseline medications. The primary outcome was time to first major adverse cardiovascular events, defined as a composite of myocardial infarction, ischemic or hemorrhagic stroke, heart failure, ventricular arrhythmia, sudden cardiac death, or all-cause mortality. Kaplan-Meier estimation and Cox proportional hazards models were used to compare outcomes over up to 10 years of follow-up. Subgroup analyses by sex, age, and race and a time-stratified analysis (≤1 year vs. >1 year follow-up) were performed.ResultsAfter matching, baseline characteristics were well balanced (mean age 51.1 years, 45% female, median HbA1c ∼7.3% in both groups). Aripiprazole was associated with a significantly elevated hazard of MACE compared to risperidone (hazard ratio [HR] 1.10, 95% confidence interval 1.02–1.18). This risk difference emerged primarily beyond the first year of treatment. The excess risk with aripiprazole was driven largely by higher rates of heart failure and ventricular arrhythmias, whereas risks of myocardial infarction and ischemic stroke were similar between groups. No significant heterogeneity in the treatment effect was observed across sex, age, or racial subgroups.ConclusionIn this large real-world cohort of patients with T2DM and schizophrenia, aripiprazole use was associated with a modest but significant increase in the risk of MACEs compared to risperidone. Clinicians should remain vigilant about cardiovascular risk management in this population regardless of antipsychotic choice. Further research is needed to elucidate mechanisms and to confirm these observations in prospective studies.